Rice allelopathy in weed management – An integrated approach - Patni, Babita; Chandra, Harish; Mishra, Abhay Prakash; Guru, Sudhir Kumar; Vitalini, Sara; Iriti, Marcello (Cellular and Molecular Biology, 2018)
The intensive use of pesticides with low biodegradability and high persistence in soil, surface and ground waters, represents a considerable environmental risk, especially under high weed pressure conditions. Furthermore, the number of herbicide-resistant weeds is increasing. Against this background, the investigation of alternative weed control strategies has taken on considerable importance. Among these, allelopathy as a negative effect of one plant on another due to the direct or indirect (including microorganisms) release of chemicals in the environment can be a useful tool for the integrated management of weeds in agroecosystems. In particular, the paddies have been considered in this work by reviewing the data both on rice allelopathy and rice weed agronomic control methods developed to improve the crop yield.